IL‐17A blockade or deficiency does not affect progressive renal fibrosis following renal ischaemia reperfusion injury in mice. (2nd June 2017) - Thorenz, Anja; Völker, Nicole; Bräsen, Jan Hinrich; Chen, Rongjun; Jang, Mi‐Sun; Rong, Song; Haller, Hermann; Kirsch, Torsten; Vieten, Gertrud; Klemann, Christian; Gueler, Faikah
Abstract: Objectives: IL‐17A contributes to acute kidney injury and fibrosis. Therefore, we asked whether IL‐17A deficiency or treatment with a IL‐17A blocking antibody impacts severe renal ischaemia reperfusion injury (IRI) and the progression to chronic kidney disease (CKD). Methods: IL‐17A‐deficient and wild‐type (WT) mice underwent transient unilateral renal pedicle clamping for 45 min to induce IRI and subsequent renal fibrosis. Furthermore, a neutralizing anti‐IL‐17A antibody (mAb) was injected into WT mice before induction of renal IRI intravenously. On days 1, 7 and 21, inflammation, fibrosis, leukocyte infiltration and pro‐inflammatory and pro‐fibrotic cytokine expression were assessed in kidneys using histology, qPCR and flow cytometry. Key findings: IL‐17A was significantly increased after renal IRI in WT kidneys. Levels of pro‐inflammatory (MCP‐1) cytokine and pro‐fibrotic (collagen 1α1, fibronectin) transcripts were similar in the experimental groups studied. IL‐17A deficiency had no effect on renal T‐cell influx or the number, inflammatory phenotype, or spatial distribution of macrophages. Similarly, administration of an IL‐17A blocking antibody did not attenuate inflammation. Conclusions: Despite the effects of IL‐17 in other inflammation models, neither genetic IL‐17A deficiency nor treatment with an IL‐17A blocking antibody attenuated IRI and progression to CKD. We conclude that in severe renal IRI IL‐17A is not crucially involved in disease progression.